Respuesta :

s1m1

Answer:

[tex]y+1=\frac{-2}{3} (x+4)[/tex]

Step-by-step explanation:

you can use the equation point-slope of a line

(y-y1)= m(x-x1)

m is the slope =rise /run

to get from the lower point  on the line to the other you rise 4 units and run -6 units so m= -4/6= -2/3

now that you have the slope pick you need one point

pick any poin on the line for example (-4, -1)

now you substitute into the point-slope equation point (-4,-1) and slope -2/3

(y+1)= -2/3(x+4)

in standard form will be

y=[tex]\frac{-2x}{3} -\frac{2*4}{3} -1[/tex]

y=[tex]\frac{-2x}{3}- \frac{5}{3}[/tex]

ACCESS MORE